Improvement of Prebiotic Properties and Resistant Starch Content of Corn Flour (Zea mays L.) Momala Gorontalo Using Physical, Chemical and Enzymatic Modification - R. Haryo Bimo Setiarto,; Muhammad Isra,; Dimas Andrianto,; Nunuk Widhyastuti,; Masrukhin, (Tropical Life Sciences Research, 2023)
Probiotics are a non-digestible food ingredient that promotes the growth of beneficial microorganisms in the intestines. One of the functional food ingredients, Momala corn flour, is a source of prebiotics with a resistant starch content of 4.42%. This study aimed to improve the prebiotic properties and resistant starch content of modified corn flour (MCF) Momala Gorontalo by using physical, chemical, and enzymatic modification processes. The research methods include physical modification (heat moisture treatment, annealing, autoclaving-cooling cycling, microwave), chemical modification (acid hydrolysis), and enzymatic modification (debranching pullulanase). The results showed that the modified by heat moisture treatment (HMT) increased RS levels 1-fold, annealing modification (ANN) 8.9-fold, autoclaving-cooling one cycle modification (AC-1C) 2.9-fold, autoclaving-cooling two cycles modification (AC-2C) 2.0-fold, microwave modification (MW) 1.3-fold, acid hydrolysis (HA) modification 5.0-fold, and debranching pullulanase (DP) modification 3.8-fold compared with corn flour control without modification. The value of the prebiotic activity of MCF hydrolysed acid (HA) is 0.03, and debranching pullulanase (DP) is 0.02 against Enteropathogenic Escherichia coli (EPEC). The prebiotic effect value of MCF HA and DP were 0.76 and 0.60, respectively. The prebiotic index value of MCF HA and DP were 0.60 and 0.48, respectively. This study confirms that MCF HA and DP are good prebiotic candidates because they have resistant starch content, low starch digestibility, and resistance to simulated gastric fluid hydrolysis than unmodified corn flour.